Machine learning system design interview : an insider's guide - Aminian, Ali; Xu, Alex (Shroff publishers, 2023)
"Machine learning system design interviews are the most difficult to tackle of all technical interview questions. This book provides a reliable strategy and knowledge base for approaching a broad range of ML system design questions. It provides a step-by-step framework for tackling an ML system design question. It includes many real-world examples to illustrate the systematic approach, with detailed steps you can follow" --Amazon